Practices of Care to HIV-Infected Children: Current Situation in Cameroon. (May 2019) - Penda, Calixte Ida; Ndongo, Francis A; Bissek, Anne-Cécile Z-K; Téjiokem, Mathurin C; Sofeu, Casimir; Moukoko Eboumbou, Else C; Mindjouli, Sandrine; Desmonde, Sophie; Njock, Louis R
Background: To accelerate access to pediatric HIV care in Cameroon, operational challenges in implementing HIV pediatric care need to be identified. The aim of this study was to assess the knowledge, attitudes, and practices of health care workers regarding pediatric HIV infection in Cameroon. Methods: A descriptive cross-sectional study was conducted over a 4-month period (April to August 2014) in 12 health facilities in 7 regions of Cameroon selected using systematic random sampling. Data were collected from interviews with health care providers and managers using standardized self-administered questionnaires and stored in the ACCESS software. Results: In total, 103 health care providers were included in this study, of which 59 (57.3%) were health workers and 44 (42.7%) community agents. Most of the health workers in charge of HIV pediatric care were nurses, requiring effective medical task shifting that was institutionalized in Cameroon. The knowledge of health care providers in relation to pediatric HIV care was acceptable. Indications for prescription of test for early infant diagnosis were known (96.1%), but their attitudes and practices regarding initiating antiretroviral therapy (ART) in infants less than 2 years (5.2%) and first-line ART protocols (25.4%) were insufficient, due to little information about standard procedures. Conclusion: Capacity building of health care providers and large-scale dissemination of normative national documents are imperative to improve HIV pediatric care in the health care facilities.